Composite borehole wall stabilizer and preparation method thereof

By adding polyelectrolyte composites and additives to the well wall stabilizer, the problem of insufficient adhesion of the well wall stabilizer is solved, and the compressive strength and deformation performance of the well wall stabilizer are significantly improved, and its use performance is improved.

CN119842372AInactive Publication Date: 2025-04-18SHAANXI HEXIN ZHONGYI OIL & GAS TECH SERVICE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510340470.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing well wall stabilizer has insufficient adhesion to the rock well wall and cannot form a precise adsorption connection relationship, resulting in poor retention performance in the well, affecting the use performance of the well wall stabilizer.

Method used

Compound well wall stabilizers, including polystyrene, acrylate, polyacrylamide, fillers, additives, potassium persulfate and defoaming agents, are used to form polyelectrolyte composites through the addition of fillers, strengthen toughness and rigidity, and improve the rigidity and steric resistance of molecules through additives.

Benefits of technology

It effectively improves the compressive strength performance and peak deformation performance of composite well wall stabilizers, and improves the use performance of well wall stabilizers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of well wall stabilizers, in particular to a composite well wall stabilizer and a preparation method thereof. The composite well wall stabilizer is prepared from, by weight, 40-60 parts of polystyrene, 30-40 parts of acrylic ester, 20-30 parts of deionized water, 20-30 parts of polyacrylamide, 10-20 parts of filler, 6-8 parts of additive, 2-4 parts of potassium persulfate and 2-4 parts of defoaming agent. According to the invention, phthalic anhydride introduces a benzene ring into xylan, the existence of the benzene ring increases the rigidity and steric hindrance of molecules, so that the movement of a xylan molecular chain is limited, the rigidity and steric hindrance of the molecules are increased, and the purpose of improving the strength performance of the well wall stabilizer is achieved; the effect of improving the toughness of the well wall stabilizer can be achieved, so that the structure of the well wall stabilizer is stable when the well wall stabilizer is stressed, and the use performance of the well wall stabilizer is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of well wall stabilizers, in particular to a composite well wall stabilizer and a preparation method thereof. Background Art

[0002] Wellbore stabilizers are chemical agents used to maintain the stability of the wellbore. They ensure the smooth progress of drilling projects by inhibiting clay expansion and preventing formation collapse.

[0003] In the prior art, the well wall stabilizer has insufficient adhesion to the rock well wall and cannot form a precise adsorption connection relationship, which makes the well wall stabilizer's retention performance in the well poor, affecting the performance of the well wall stabilizer. Based on this, the present invention provides a composite well wall stabilizer and a preparation method thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a composite well wall stabilizer and a preparation method thereof. The composite well wall stabilizer prepared by the present invention not only has good compressive strength performance, but also has excellent breaking load peak deformation performance, which effectively improves the use performance of the composite well wall stabilizer.

[0005] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a composite well wall stabilizer, comprising the following raw materials in parts by weight: 40 to 60 parts of polystyrene, 30 to 40 parts of acrylate, 20 to 30 parts of deionized water, 20 to 30 parts of polyacrylamide, 10 to 20 parts of filler, 6 to 8 parts of additives, 2 to 4 parts of potassium persulfate and 2 to 4 parts of defoaming agent; The raw materials of the filler consist of chitosan, sodium alginate, rubber powder, lignin, starch and rosin.

[0006] Furthermore, the mass ratio of the chitosan, sodium alginate, rubber powder, lignin, starch and rosin is 1: (0.4-0.6): (0.2-0.4): (2-3): (0.2-0.4): (0.1-0.3).

[0007] Furthermore, the filler is prepared by the following method: chitosan and sodium alginate are mixed in a water bath, a dilute acetic acid solution is added to a beaker, the mass of the dilute acetic acid solution is 2 to 3 times the mass of chitosan, and the concentration of the dilute acetic acid solution is 3 to 5%, the water bath is set to heat up to 40 to 50°C, and a magnetic stirrer is used at 100 to 200 r / min for heat preservation and stirring for 6 to 10 minutes to obtain a mixed solution.

[0008] Furthermore, the rubber powder uses waste tires as raw materials, the waste tires are recycled and then cleaned, crushed, ground and dried, and the particle size of the ground tires is 10-20 μm to obtain rubber powder.

[0009] Furthermore, lignin and rubber powder are added to a mixer, which is set at 500-700 r / min and stirred for 10-20 min. The mixed product is added to an internal mixer, which is set at 100-160° C., with a stirring speed of 60-100 r / min, and kneaded for 6-10 min to obtain a mixture.

[0010] Furthermore, starch and rosin are added to a reactor, water is added to the reactor, the mass of the water is 1.5 to 2.5 times the mass of the starch, the reactor is set to be heated to 60 to 70°C, the stirring speed is 200 to 300 r / min, and the heat preservation and stirring treatment is carried out for 20 to 30 minutes, and then the mixed liquid and the mixed material are added, and the reactor repeats the above heat preservation and stirring treatment to obtain the filler, wherein the starch is corn starch and the rosin is granular material with a particle size of 1 to 3 mm.

[0011] Furthermore, the additive is prepared by the following method: xylan and N,N-dimethylformamide are mixed in a water bath, the water bath is set to heat up to 50-70°C, the reaction is kept warm for 10 minutes, triethylamine is added, the water bath is connected to a magnetic stirrer, the temperature is set at 160-200r / min, and the stirring treatment is kept warm for 4-6 minutes, phthalic anhydride is added, and the above-mentioned stirring treatment is repeated, the obtained product is filtered, and the N,N-dimethylformamide is recovered by distillation to obtain a filter cake, the filter cake is washed with deionized water, and then sent to an oven, and the oven is set at 50-60°C for drying for 20-30 minutes to obtain the additive.

[0012] Furthermore, the mass ratio of the xylan to N,N-dimethylformamide is 1:(0.1-0.3), the mass of the triethylamine is 5-7% of the mass of the xylan, and the mass of the phthalic anhydride is 8-10% of the mass of the xylan.

[0013] Furthermore, the defoaming agent is a silicone defoaming agent.

[0014] In a second aspect, the present invention also provides a method for preparing a composite well wall stabilizer, comprising the following steps: S1: Weigh polystyrene, acrylate, deionized water and polyacrylamide as needed and add them into a reactor. Set the reactor to heat up to 40-60°C, stir at 200-300 r / min, and stir for 10-20 min to obtain a primary mixture. S2: Fillers, additives, potassium persulfate and defoaming agent are weighed and added to the primary mixture as required, the reactor is set to heat up to 70-80°C, the stirring speed is 300-400r / min, and the mixture is stirred at this temperature for 20-30min. The obtained product is dried to obtain a composite well wall stabilizer.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. In the present invention, additives are added during the preparation of the composite wellbore stabilizer, wherein triethylamine is used as a catalyst to promote the reaction of xylan and phthalic anhydride. Phthalic anhydride introduces benzene rings into xylan. The presence of benzene rings increases the rigidity and steric hindrance of the molecule, restricts the movement of the xylan molecular chain, increases the molecular rigidity and steric hindrance, and achieves the purpose of improving the strength performance of the wellbore stabilizer. At the same time, the good flexibility of the xylan molecular chain can be used to improve the toughness of the wellbore stabilizer, so that the structure of the wellbore stabilizer is relatively stable when subjected to force, thereby effectively improving the performance of the wellbore stabilizer.

[0016] 2. In the present invention, by adding fillers, chitosan and sodium alginate can be mixed to form a polyelectrolyte complex. The network structure of the polyelectrolyte complex can wrap and fix the mixture of lignin and rubber powder and the reaction products of starch and rosin, so that they form a relatively stable overall structure in the well wall stabilizer, thereby enhancing the toughness and rigidity of the polyelectrolyte complex. The reaction products of starch and rosin fill the gaps in the network structure, further improving the density and adhesion of the well wall stabilizer, thereby effectively improving the performance of the well wall stabilizer. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] It should be noted that the raw materials used in the following examples are all commercially available raw materials.

[0019] Embodiment 1:

[0020] A composite well wall stabilizer, comprising the following raw materials in parts by weight: 40 parts of polystyrene, 30 parts of acrylate, 20 parts of deionized water, 20 parts of polyacrylamide, 10 parts of filler, 6 parts of additives, 2 parts of potassium persulfate and 2 parts of defoamer; The raw materials of the filler consist of chitosan, sodium alginate, rubber powder, lignin, starch and rosin.

[0021] Furthermore, the mass ratio of chitosan, sodium alginate, rubber powder, lignin, starch and rosin is 1:(0.4):(0.2):(2):(0.2):(0.1).

[0022] Furthermore, the filler is prepared by the following method: chitosan and sodium alginate are mixed in a water bath, a dilute acetic acid solution is added to a beaker, the mass of the dilute acetic acid solution is twice the mass of chitosan, the concentration of the dilute acetic acid solution is 3%, the water bath is set to heat up to 40°C, and a magnetic stirrer is used at 100r / min for 6 minutes to obtain a mixed solution.

[0023] Furthermore, the rubber powder uses waste tires as raw materials. The waste tires are recycled and cleaned, and then crushed, ground and dried. The particle size of the ground tires is 10 μm to obtain rubber powder.

[0024] Furthermore, lignin and rubber powder were added to a mixer, which was set at 500 r / min for 10 min of stirring. The mixed product was added to an internal mixer, which was set at 100° C. and a stirring speed of 60 r / min for 6 min of mixing to obtain a mixture.

[0025] Furthermore, starch and rosin are added to a reactor, and water is added to the reactor, the mass of the water is 1.5 times the mass of the starch, the reactor is set to be heated to 60°C, the stirring speed is 200r / min, and the heat preservation and stirring treatment is carried out for 20 minutes, and then the mixed liquid and the mixed material are added, and the reactor repeats the above heat preservation and stirring treatment to obtain the filler, wherein the starch is corn starch and the rosin is granular material with a particle size of 1mm.

[0026] Furthermore, the additive is prepared by the following method: xylan and N,N-dimethylformamide are mixed in a water bath, the water bath is set to heat up to 50°C, the reaction is kept warm for 10 minutes, triethylamine is added, the water bath is connected to a magnetic stirrer, the temperature is set to 160r / min and the mixture is kept warm and stirred for 4 minutes, phthalic anhydride is added, the above-mentioned warm and stirring treatment is repeated, the obtained product is filtered, and the N,N-dimethylformamide is recovered by distillation to obtain a filter cake, the filter cake is washed with deionized water, and then sent to an oven, and the oven is set to 50°C for drying for 20 minutes to obtain the additive.

[0027] Furthermore, the mass ratio of xylan to N,N-dimethylformamide is 1:(0.1), the mass of triethylamine is 5% of the mass of xylan, and the mass of phthalic anhydride is 8% of the mass of xylan.

[0028] Furthermore, the defoaming agent is a silicone defoaming agent.

[0029] A method for preparing a composite well wall stabilizer comprises the following steps: S1: Weigh polystyrene, acrylate, deionized water and polyacrylamide as needed and add them into a reactor. Set the reactor to heat up to 40°C, stir at a speed of 200 r / min, and stir for 10 minutes to obtain a primary mixture. S2: Fillers, additives, potassium persulfate and defoaming agent are weighed and added to the primary mixture as required. The reactor is set to heat up to 70°C, with a stirring speed of 300 r / min. The mixture is stirred at this temperature for 20 minutes. The obtained product is dried to obtain a composite well wall stabilizer.

[0030] Embodiment 2:

[0031] A composite well wall stabilizer, comprising the following raw materials in parts by weight: 50 parts of polystyrene, 35 parts of acrylate, 25 parts of deionized water, 25 parts of polyacrylamide, 15 parts of filler, 7 parts of additives, 3 parts of potassium persulfate and 3 parts of defoamer; The raw materials of the filler consist of chitosan, sodium alginate, rubber powder, lignin, starch and rosin.

[0032] Furthermore, the mass ratio of chitosan, sodium alginate, rubber powder, lignin, starch and rosin is 1:(0.5):(0.3):(2.5):(0.3):(0.2).

[0033] Furthermore, the filler is prepared by the following method: chitosan and sodium alginate are mixed in a water bath, a dilute acetic acid solution is added to a beaker, the mass of the dilute acetic acid solution is 2.5 times the mass of chitosan, and the concentration of the dilute acetic acid solution is 4%, the water bath is set to heat up to 45°C, and a magnetic stirrer is used at 150r / min for 8 minutes to obtain a mixed solution.

[0034] Furthermore, the rubber powder uses waste tires as raw materials. The waste tires are recycled and then cleaned. After cleaning, they are crushed, ground and dried. The particle size of the ground tires is 15 μm to obtain rubber powder.

[0035] Furthermore, lignin and rubber powder were added to a mixer, which was set at 600 r / min for 15 min of stirring. The mixed product was added to an internal mixer, which was set at 130° C. and a stirring speed of 80 r / min for 8 min of mixing to obtain a mixture.

[0036] Furthermore, starch and rosin are added to a reactor, and water is added to the reactor, the mass of the water is twice the mass of the starch, the reactor is heated to 65°C, the stirring speed is 260r / min, and the heat preservation and stirring treatment is carried out for 25 minutes, and then the mixed liquid and the mixed material are added, and the reactor repeats the above heat preservation and stirring treatment to obtain the filler, wherein the starch is corn starch and the rosin is granular material with a particle size of 2mm.

[0037] Furthermore, the additive is prepared by the following method: xylan and N,N-dimethylformamide are mixed in a water bath, the water bath is set to heat up to 60°C, the reaction is kept warm for 10 minutes, triethylamine is added, the water bath is connected to a magnetic stirrer, the temperature is set to 180r / min and the mixture is kept warm and stirred for 5 minutes, phthalic anhydride is added, the above-mentioned warm and stirring treatment is repeated, the obtained product is filtered, and the N,N-dimethylformamide is recovered by distillation to obtain a filter cake, the filter cake is washed with deionized water, and then sent to an oven, the oven is set to 55°C and dried for 25 minutes to obtain the additive.

[0038] Furthermore, the mass ratio of xylan to N,N-dimethylformamide is 1:(0.2), the mass of triethylamine is 6% of the mass of xylan, and the mass of phthalic anhydride is 9% of the mass of xylan.

[0039] Furthermore, the defoaming agent is a silicone defoaming agent.

[0040] A method for preparing a composite well wall stabilizer comprises the following steps: S1: Weigh polystyrene, acrylate, deionized water and polyacrylamide as needed and add them into a reactor. Set the reactor to heat up to 50°C, stir at 260r / min, and stir for 15 minutes to obtain a primary mixture. S2: Fillers, additives, potassium persulfate and defoaming agent are weighed and added to the primary mixture as required. The reactor is set to heat up to 75°C, with a stirring speed of 350 r / min. The mixture is stirred at this temperature for 25 minutes. The obtained product is dried to obtain a composite well wall stabilizer.

[0041] Embodiment three:

[0042] A composite well wall stabilizer comprises the following raw materials in parts by weight: 60 parts of polystyrene, 40 parts of acrylate, 30 parts of deionized water, 30 parts of polyacrylamide, 20 parts of filler, 8 parts of additives, 4 parts of potassium persulfate and 4 parts of defoamer; The raw materials of the filler consist of chitosan, sodium alginate, rubber powder, lignin, starch and rosin.

[0043] Furthermore, the mass ratio of chitosan, sodium alginate, rubber powder, lignin, starch and rosin is 1:(0.6):(0.4):(3):(0.4):(0.3).

[0044] Furthermore, the filler is prepared by the following method: chitosan and sodium alginate are mixed in a water bath, a dilute acetic acid solution is added to a beaker, the mass of the dilute acetic acid solution is 3 times the mass of chitosan, the concentration of the dilute acetic acid solution is 5%, the water bath is set to heat up to 50°C, and a magnetic stirrer is used at 200r / min for 10 minutes to obtain a mixed solution.

[0045] Furthermore, the rubber powder uses waste tires as raw materials. The waste tires are recycled and then cleaned. After cleaning, they are crushed, ground and dried. The particle size of the ground tires is 20 μm to obtain rubber powder.

[0046] Furthermore, lignin and rubber powder were added to a mixer, which was set at 700 r / min for 20 min of stirring. The mixed product was added to an internal mixer, which was set at 160° C. and a stirring speed of 100 r / min for 10 min of mixing to obtain a mixture.

[0047] Furthermore, starch and rosin are added to a reactor, and water is added to the reactor, the mass of the water is 2.5 times the mass of the starch. The reactor is set to be heated to 70°C, the stirring speed is 300r / min, and the heat preservation and stirring treatment is carried out for 30 minutes. After that, the mixed liquid and the mixed material are added, and the reactor repeats the above heat preservation and stirring treatment to obtain the filler, wherein the starch is corn starch and the rosin is granular material with a particle size of 3mm.

[0048] Furthermore, the additive is prepared by the following method: xylan and N,N-dimethylformamide are mixed in a water bath, the water bath is set to heat up to 70°C, the reaction is kept warm for 10 minutes, triethylamine is added, the water bath is connected to a magnetic stirrer, the temperature is set to 200r / min and the mixture is kept warm and stirred for 6 minutes, phthalic anhydride is added, the above-mentioned warm and stirring treatment is repeated, the obtained product is filtered, and the N,N-dimethylformamide is recovered by distillation to obtain a filter cake, the filter cake is washed with deionized water, and then sent to an oven, and the oven is set to 60°C for drying for 30 minutes to obtain the additive.

[0049] Furthermore, the mass ratio of xylan to N,N-dimethylformamide is 1:(0.3), the mass of triethylamine is 7% of the mass of xylan, and the mass of phthalic anhydride is 10% of the mass of xylan.

[0050] Furthermore, the defoaming agent is a silicone defoaming agent.

[0051] A method for preparing a composite well wall stabilizer comprises the following steps: S1: Weigh polystyrene, acrylate, deionized water and polyacrylamide as needed and add them into a reactor. Set the reactor to heat up to 60°C, stir at 300 r / min, and stir for 20 minutes to obtain a primary mixture. S2: Fillers, additives, potassium persulfate and defoaming agent are weighed and added to the primary mixture as required. The reactor is set to heat up to 80°C, with a stirring speed of 400 r / min. The mixture is stirred at this temperature for 30 minutes. The obtained product is dried to obtain a composite well wall stabilizer.

[0052] Comparative Example 1: The difference between this comparative example and Example 1 is that triethylamine is not added when preparing the additive in this comparative example.

[0053] Comparative Example 2: The difference between this comparative example and Example 1 is that in this comparative example, no phthalic anhydride is added when preparing the additive.

[0054] Comparative Example 3: The difference between this comparative example and Example 1 is that this comparative example does not contain filler.

[0055] Comparative Example 4: The difference between this comparative example and Example 1 is that this comparative example does not contain any additive.

[0056] Performance test: The composite wellbore stabilizers prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were subjected to performance tests, and the obtained test data are recorded in the following table:

[0057] In the performance test, a standard core skeleton was made, and the composite wellbore stabilizers prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were respectively added to the core skeletons, and the compressive state of each core skeleton was tested at room temperature using a dynamic rock strength evaluation system.

[0058] It can be seen that the compressive strength performance and the breaking load peak deformation performance of the composite well wall stabilizer prepared in comparative examples 1, 2, 3 and 4 are lower than those in embodiments 1, 2 and 3; this shows that: by adding additives in the preparation process of the composite well wall stabilizer, wherein the addition of triethylamine is used as a catalyst to promote the reaction of xylan and phthalic anhydride, phthalic anhydride introduces benzene rings into xylan, and the presence of benzene rings increases the rigidity and steric hindrance of the molecule, restricts the movement of the xylan molecular chain, increases the molecular rigidity and steric hindrance, and achieves the purpose of improving the strength performance of the well wall stabilizer. At the same time, the good flexibility of the xylan molecular chain can be used to improve the well wall stability. The toughness of the stabilizer makes the structure of the well wall stabilizer more stable when subjected to stress, effectively improving the performance of the well wall stabilizer. By adding fillers, chitosan and sodium alginate can be mixed to form a polyelectrolyte complex. The network structure of the polyelectrolyte complex can wrap and fix the mixture of lignin and rubber powder and the reaction products of starch and rosin, so that they form a relatively stable overall structure in the well wall stabilizer, enhancing the toughness and rigidity of the polyelectrolyte complex. The reaction products of starch and rosin fill the gaps in the network structure, further improving the density and adhesion of the well wall stabilizer, thereby effectively improving the performance of the well wall stabilizer.

[0059] By comparing and analyzing the relevant data in the table, it can be seen that the composite well wall stabilizer prepared by the present invention not only has good compressive strength performance, but also has excellent breaking load peak deformation performance. This shows that the composite well wall stabilizer provided by the present invention has a broader market prospect and is more suitable for promotion.

[0060] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0061] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A composite well wall stabilizer, characterized in that: The method comprises the following raw materials in parts by weight: 40 to 60 parts of polystyrene, 30 to 40 parts of acrylate, 20 to 30 parts of deionized water, 20 to 30 parts of polyacrylamide, 10 to 20 parts of filler, 6 to 8 parts of additives, 2 to 4 parts of potassium persulfate and 2 to 4 parts of defoaming agent; The raw materials of the filler consist of chitosan, sodium alginate, rubber powder, lignin, starch and rosin.

2. The composite wellbore stabilizer according to claim 1, characterized in that: The mass ratio of the chitosan, sodium alginate, rubber powder, lignin, starch and rosin is 1: (0.4-0.6): (0.2-0.4): (2-3): (0.2-0.4): (0.1-0.3).

3. The composite wellbore stabilizer according to claim 1, characterized in that: The filler is prepared by the following method: chitosan and sodium alginate are mixed in a water bath, a dilute acetic acid solution is added into a beaker, the mass of the dilute acetic acid solution is 2 to 3 times the mass of the chitosan, the concentration of the dilute acetic acid solution is 3 to 5%, the water bath is set to heat up to 40 to 50° C., and a magnetic stirrer is used at 100 to 200 r / min for heat preservation and stirring for 6 to 10 minutes to prepare a mixed solution.

4. The composite well wall stabilizer according to claim 3, characterized in that: The rubber powder is made of waste tires, which are recycled and cleaned, crushed, ground and dried, with a particle size of 10 to 20 μm to obtain the rubber powder.

5. The composite wellbore stabilizer according to claim 4, characterized in that: Lignin and rubber powder are added to a mixer, which is set at 500-700 r / min and stirred for 10-20 min. The mixed product is added to an internal mixer, which is set at 100-160° C., with a stirring speed of 60-100 r / min, and kneaded for 6-10 min to obtain a mixture.

6. The composite wellbore stabilizer according to claim 5, characterized in that: Starch and rosin are added into a reactor, water is added into the reactor, the mass of the water is 1.5 to 2.5 times of the mass of the starch, the reactor is heated to 60 to 70°C, the stirring speed is 200 to 300 r / min, the reactor is kept warm and stirred for 20 to 30 minutes, then the mixed liquid and the mixed material are added, the reactor is repeated with the above-mentioned heat preservation and stirring treatment to obtain the filler, wherein the starch is corn starch, and the rosin is granular material with a particle size of 1 to 3 mm.

7. The composite wellbore stabilizer according to claim 1, characterized in that: The additive is prepared by the following method: xylan and N,N-dimethylformamide are mixed in a water bath, the water bath is set to heat up to 50-70°C, the temperature is kept warm for reaction for 10 minutes, triethylamine is added, the water bath is connected to a magnetic stirrer, the temperature is set at 160-200r / min, and the temperature is kept warm and stirred for 4-6 minutes, phthalic anhydride is added, the temperature is kept warm and stirred for 4-6 minutes, the product is filtered, and the N,N-dimethylformamide is recovered by distillation to obtain a filter cake, the filter cake is washed with deionized water, and then sent to an oven, the oven is set at 50-60°C for drying for 20-30 minutes to obtain the additive.

8. The composite well wall stabilizer according to claim 7, characterized in that: The mass ratio of xylan to N,N-dimethylformamide is 1:(0.1-0.3), the mass of triethylamine is 5-7% of the mass of xylan, and the mass of phthalic anhydride is 8-10% of the mass of xylan.

9. The composite wellbore stabilizer according to claim 1, characterized in that: The defoaming agent is an organosilicon defoaming agent.

10. A method for preparing the composite well wall stabilizer according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Weigh polystyrene, acrylate, deionized water and polyacrylamide as needed and add them into a reactor. Set the reactor to heat up to 40-60°C, stir at 200-300 r / min, and stir for 10-20 min to obtain a primary mixture. S2: Fillers, additives, potassium persulfate and defoaming agent are weighed and added to the primary mixture as required, the reactor is set to heat up to 70-80°C, the stirring speed is 300-400r / min, and the mixture is stirred at this temperature for 20-30min. The obtained product is dried to obtain a composite well wall stabilizer.

Citation Information

Patent Citations

  • Self-healing gel leakage-proof agent while drilling under covalent bond-non-covalent bond composite action and preparation method and application thereof

    CN113943558A

  • Plugging anti-leakage agent as well as preparation method and application thereof

    CN117821038A

  • Well wall stabilizer and preparation method thereof

    CN118255935A

  • Multi-component copolymer and preparation method therefor and use thereof

    WO2024255789A1